The rising burden of diabetes and state-wise variations in India: insights from the Global Burden of Disease Study 1990–2021 and projections to 2031 - Shubham Chauhan; Mahalaqua Nazli Khatib; Suhas Ballal; Pooja Bansal; Kiran Bhopte; Abhay M. Gaidhane; Balvir S. Tomar; Ayash Ashraf; M. Ravi Kumar; Ashish Singh Chauhan; Muhammed Shabil; Diptismita Jena; et al. (Frontiers in Endocrinology)
BackgroundDiabetes is a major public health concern in India, contributing significantly to morbidity and mortality. With variations in disease burden across states, a detailed understanding of trends in incidence, prevalence, and Disability Adjusted Life Years (DALYs) is essential for targeted interventions.MethodsThis study utilized Global Burden of Disease (GBD) data from 1990 to 2021 to examine trends in diabetes across Indian states. Age-standardized incidence, prevalence, mortality, and DALYs were analyzed using Join point regression to estimate Annual Percentage Change (APC). Autoregressive Integrated Moving Average (ARIMA) models were employed to project diabetes trends up to 2031.While the GBD data provide robust national and regional estimates, their modeled nature may not capture the full spectrum of local epidemiological variations.ResultsDiabetes incidence increased from 162.74 to 264.53 per 100,000 between 1990 and 2021, with an APC of 0.63%. Joinpoint analysis identified episodic surges in incidence, with APCs of 2.25% during 1996–1999 and 2.07% during 2005–2011, suggesting intervals of accelerated increase relative to the gradual progression typically observed in chronic conditions. Mortality rose from 23.09 to 31.12 per 100,000 (APC: 0.12%). Southern and Western states, such as Tamil Nadu and Goa, exhibited the highest prevalence and DALYs. Forecasted trends indicate that by 2031, the prevalence will reach 8585.45 per 100,000, and DALYs will exceed 1241.57 per 100,000.ConclusionThe burden of diabetes in India has risen markedly over the past three decades. These findings underscore the urgent need for health policies that emphasize lifestyle modifications and improved healthcare access. A comprehensive approach that integrates primary prevention through community-based health education, dietary counseling, and initiatives to promote physical activity with secondary prevention measures such as systematic screening and timely clinical management, is essential for effective diabetes control and management in high-burden states.